1988
DOI: 10.1203/00006450-198810000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Cord Plasma Vasopressin, Erythropoietin, and Hypoxanthine as Indices of Asphyxia at Birth

Abstract: ABSTRACT. To assess the value of cord plasma arginine vasopressin (AVP), erythropoietin (EP), and hypoxanthine (HX) as indices of asphyxia, we studied 62 infants of mothers with preeclampsia, 34 acutely asphyxiated infants, with 5-min Apgar score 5 6 and/or umbilical arterial pH 57.05, and 38 control infants. Umbilical arterial AVP in the asphyxia group (geometric mean; 95% confidence interval: 180; 92-350 pg/ml) was higher than in the control group (23; 8-66, p = 0.002) and correlated with umbilical arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
1
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 24 publications
1
29
1
2
Order By: Relevance
“…11 Similar to the study done by Ramesh R Pol et al, there is significant difference found in the values of hemoglobin between cases and controls. 5 But unlike their study, significant difference was not found in value of hematocrit when compared between cases and controls. Similar to finding in their study, leucocyte count was higher among the cases with highest among the HIE-III cases which may be due to the oxidative stress present during birth.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…11 Similar to the study done by Ramesh R Pol et al, there is significant difference found in the values of hemoglobin between cases and controls. 5 But unlike their study, significant difference was not found in value of hematocrit when compared between cases and controls. Similar to finding in their study, leucocyte count was higher among the cases with highest among the HIE-III cases which may be due to the oxidative stress present during birth.…”
Section: Discussioncontrasting
confidence: 48%
“…Many acute and chronic stimuli cause increase in the number of circulating n-RBCs from either increased erythropoetic activity or a sudden release from the marrow storage pools. 5 The number of n-RBC /100 WBCs is variable but is rarely more than 10 6-8 . Frequent conditions like prematurity, rhesus sensitization, in which the number of n-RBCs exceeds 10, have been excluded from our study.…”
Section: Discussionmentioning
confidence: 99%
“…[35] Traditionally it has been thought that EPO, in response to hypoxia, is the main driving force behind NRBC production. [36,37] It has also been thought that the duration and severity of fetal hypoxia may be predicted by the number of increased NRBCs in the neonates delivered both preterm and at term. [12,33,38] Recent data has questioned whether hypoxia is the sole mechanism responsible for an increase in the fetal NRBC.…”
Section: Discussionmentioning
confidence: 99%
“…A asfixia também desencadeia um rápido aumento na secreção de vários hormônios, entre eles catecolaminas 2 , glicocorticóides [2][3][4] , ACTH 4 , ß-endorfinas 4 , hormônio antidiurético [5][6][7][8] , aldosterona 1,2,9,10 , renina 11 e peptídeo atrial natriurético 9,12 , bem como uma diminuição na insulina 1 .…”
unclassified